An Open-Source BioMEMS Platform for Generalized Early Cancer Detection - Silva, Lucca Reinehr; Sulzbach, Joao Frischenbruder; Nunes, Joao Pedro Perin; E Silva Lobo De Almeida, Thales Vieira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Cancer remains one of the most pressing challenges for humanity, with early detection significant for improving survival rates. Open-source initiatives have revolutionized various fields by fostering collaboration, broadening impact, and democratizing access to resources. We propose to expand this ethos to cancer research, introducing a versatile biosensing framework developed using open-source tools only. This biosensor is capable of detecting diverse types of cancer simultaneously, or detecting a single type with enhanced sensitivity. To validate the platform, a proof-of-concept design is presented, and limitations of the current open-source ecosystem are discussed.
Keywords: biomarkers; biosensors; cancer; coupled resonators; MEMS; open-source; open-source silicon